Chromosome Abnormalities in Peripheral Blood Cells of Post-Polio Patients in South Indian Population - Sengupta1 and J.C. AustinÂ², Saurabh Kumar BhattacharyaÂ¹* Sonali (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">A number of viruses have been shown to be capable of producing abnormalities of the metaphase chromosomes in circulating lymphocytes during some natural infections in man, i.e., measles virus, chicken pox and mumps viruses and hepatitis virus. However this cataloguing of viruses with a demonstrated capacity for direct or indirect production of effects on metaphase chromosomes is most certainly incomplete. Thus even the immediate effects of a high number of viral genomes, important one being poliovirus on chromosome is still wanting. Further follow up studies on the delayed late effects of viral genome on the human leukocyte chromosomes was much less in literature. Hence to fulfil the lacunae a study is undertaken to investigate mainly the delayed effects of polio virus on human chromosomes in post polio syndrome. The control group consisted of 30 healthy subjects for chromosomal aberration analysis. All the control subjects were matched for age and with no history of Polio. The study group consisted of 30 Polio patients for analysis of cytogenetic aberration. The details of sex, age at onset, severity of disease, exposure to chemicals, smoking and consanguinity is presented for the 30 PPS individuals. In this study the frequency of chromosome aberrations in PPS showed a significant increase as compared with the controls.